Lack of bystander activation shows that localization exterior to chromosome territories is not sufficient to up-regulate gene expression - Morey, Céline; Kress, Clémence; Bickmore, Wendy A. (Genome Research, 2009)
Position within chromosome territories and localization at transcription factories are two facets of nuclear organization that have been associated with active gene expression. However, there is still debate about whether this organization is a cause or consequence of transcription. Here we induced looping out from chromosome territories (CTs), by the activation of Hox loci during differentiation, to investigate consequences on neighboring loci. We show that, even though flanking genes are caught up in the wave of nuclear reorganization, there is no effect on their expression. However, there is a differential organization of active and inactive alleles of these genes. Inactive alleles are preferentially retained within the CT, whereas actively transcribing alleles, and those associated with transcription factories, are found both inside and outside of the territory. We suggest that the alleles relocated further to the exterior of the CT are those that were already active and already associated with transcription factories before the induction of differentiation. Hence active gene regions may loop out from CTs because they are able to, and not because they need to in order to facilitate gene expression.
10.1101/gr.089045.108